Traumatic Recurrent Hip Dislocation Associated With Femoral Head Fracture Reconstructed With Iliac Crest Autograft (International Journal of Medical and Surgical Sciences, 2021)
Hip femoral head fractures are extremely uncommon, but likely associated with traumatic hip dislocations. Both lesions require emergent treatment to avoid further complications.19-year-old male patient was received after a high-energy motor vehicle accident with severe brain and thoraco-abdominal trauma and a displaced femoral head fracture with posterior hip dislocation with no acetabular fracture. An emergent open reduction and internal fixation with 2 headless screws was performed, as well as posterior capsule repair. After 1 month as an inpatient in Intensive Care Unit, he sustained a new episode of posterior hip dislocation. Consequently, a second successful surgical reduction was obtained, and hip stability was achieved by posterior reconstruction with iliac crest autograft fixed with cannulated screw and posterior structure repair. Two  years later, he was able to walk independently and he does not present any signs of degenerative joint disease nor avascular necrosis.
Keywords: femoral head fracture; recurrent native hip dislocation; iliac crest graft; posterior hip reconstruction; polytrauma